REANALYSIS OF SPIN-OFF ISLAMIC BANKS IN INDONESIA: EFFICIENT OR NOT? - M Fuad Hadziq; yosi mardoni; syafwendi syafril (Univeristas Islam Bandung, 2022)
The market share of Islamic banks in Indonesia is around 6,3%. Although starting 2008, BI had been a spin-off to enrich the Islamic bank market share, the efficiency did not surmount the big problem from an Islamic bank. This study aims to reanalysis efficiency policy in Indonesia's spin-off in 2011-2019. The research sample is Islamic banking in Indonesia, including BUS (Islamic commercial banks) and UUS (Sharia Business Unit) that was doing spin-off yet. This research used an analysis method of DEA (Data Envelopment Analysis) by using CRS (constant return to scale) and VRS (Variable return to scale models). The variables consisted of input and output, such as liquid assets, total financing, profit-sharing income, operating cost, personnel cost, and fixed assets. The result and findings show that BUS after the spin-off is inefficient. Moreover, several Islamic commercial banks decreased inefficiency in many periods. The spin-off does not affect efficiency, especially in the market share of Islamic banks. UUS was more efficient than BUS. One of the factors because of operational cost. However, the BUS is more inefficient than UUS in producing Islamic financial products and services. Besides that, labor costs cannot cut and always grow every time. Finally, making a load of the company to be weight thus consumer prize more expensive